The Effect of Principal Leadership on the Teaching Performance of Elementary School Teachers and Their Impact on School Quality in Lebak-Banten District - Ratnasari, Dine Trio; Saud, Udin Syaefudin; Agustin, Mubiar; Permana, Johar (International Conference on Elementary Education, 2022)
An elementary school quality success is strongly influenced by the teaching performance of teachers. To achieve this success requires a strong foundation from the teachers, including the leadership of the principal. For elementary schools in Lebak Regency, this is a challenge for teachers in Lebak Regency to produce good school quality standards. This study aims to analyze the effect of discipline, motivation, school facilities and principal leadership on teacher teaching performance which has an impact on the quality of elementary schools in Lebak Regency, so as to determine the success rate of discipline, motivation, school facilities, and leadership given by the principal. The population in this study were all elementary school teachers in Lebak Regency, a total of 775 people. Due to the limitations of distance and time, the sampling in this study was using the purposive random sampling method, thus obtaining a total of 100 respondents. The data was collected using a questionnaire to the respondents. To answer the problems in research and testing research hypotheses, the Partial Least Square (PLS) analysis technique is used using the SmartPLS software. The results of this study indicate that 1) principal leadership has an effect of 86% on teacher teaching performance, 2) teacher teaching performance has an effect of 76% on school quality. The data was taken from a descriptive analysis of the answers agree and strongly agree on the questionnaire given. The data was collected using a questionnaire to the respondents. To answer the problems in research and testing research hypotheses, the Partial Least Square (PLS) analysis technique is used using the SmartPLS software. The results of this study indicate that 1) the principal's leadership has an effect of 86% on the teaching performance of teachers, 2) the teacher's teaching performance has an effect of 76% on the quality of the school. The data was taken from a descriptive analysis of the answers agree and strongly agree on the questionnaire given. The data was collected using a questionnaire to the respondents. To answer the problems in research and testing research hypotheses, the Partial Least Square (PLS) analysis technique is used using the SmartPLS software. The results of this study indicate that 1) principal leadership has an effect of 86% on teacher teaching performance, 2) teacher teaching performance has an effect of 76% on school quality. The data was taken from a descriptive analysis of the answers agree and strongly agree on the questionnaire given. The results of this study indicate that 1) principal leadership has an effect of 86% on teacher teaching performance, 2) teacher teaching performance has an effect of 76% on school quality. The data was taken from a descriptive analysis of the answers agree and strongly agree on the questionnaire given. The results of this study indicate that 1) principal leadership has an effect of 86% on teacher teaching performance, 2) teacher teaching performance has an effect of 76% on school quality. The data was taken from a descriptive analysis of the answers agree and strongly agree on the questionnaire given.